La práctica de actividad física en población universitaria: etapas del cambio, motivación, percepción y su relación con la regulación emocional (2020)
The stages of change are changes in the behavior of a person, who follows a series of steps to achieve a goal. Various reasons have been evidenced for the realization physical exercise; however, emotional regulation is not one that is frequently evidenced in the literature. The present study aimed to determine how much those who perform aerobic physical exercise identifies if it has an effect on the management of their emotions in order to understand if emotional regulation is an implicit motive for physical exercise. Likewise, it was determined if the stages of change of the Transtheoretical Model of Change (TTM) had any relationship with the reasons for physical activity. A quantitative approach was used, descriptive and correlational design. The sample was composed by 231 students from different private universities in Bogotá. The scale of Motives for Physical Activity (MPAM-R) was used as well as the Scale of Difficulties for Emotional Regulation (DERS)...